Pengaruh Permainan Small Side Games terhadap Lari Kecepatan 10 Meter pada Cabang Olahraga Sepak Bola Akademi Persib U-17 - Bagerry, Muhammad Moreno; Imanudin, Iman; Hardwis, Syam; Fadli, Muhamad (Universitas Nusantara PGRI Kediri, 2025)
Speed ​​is one of the important aspects of physical condition in athletics, especially those involving fast movements such as soccer. This study aims to determine the effectiveness of the Small Side Games training method in increasing speed in soccer players aged 17-18 years. The research method used is an experimental design with a pre-experimental approach (pre-test, post-test design), where speed measurements were taken before and after treatment. The subjects of the study consisted of 30 Persib Bandung Academy athletes who participated in training for 5 weeks with a total of 15 meetings. Training was given three times a week with the application of the progressive overload principle, namely increasing training volume through training duration. The results of the study showed that the application of Small Side Games training did not provide significant changes in increasing speed in soccer athletes aged 17-18 years. This finding provides an illustration that this training method may need further adjustment to increase its effectiveness in increasing speed.